2016
DOI: 10.5964/ijpr.v10i1.208
|View full text |Cite
|
Sign up to set email alerts
|

Intimate relationships and attitudes toward celebrities

Abstract: Previous research indicates that persons who self-report a high level of preoccupation with celebrities tend to have lower levels of well-being. We administered the "Romantic Partner Conflict Scale", the "Love Attitudes Scale", the soulmate subscale from the "Relationship Theories Questionnaire", and the anxiety subscale from the "Experiences in Close Relationships Scale" to 330 students from four universities to see how well scores on these measures would predict scores on each of the three subscales from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…In this study, for participants from the USA, 'game-playing' love style was associated with intense-personal CWalthough the two appeared unrelated in participants from India. McCutcheon et al (2016e) noted relationships between intense-personal CW and both 'practical' and 'dependent' love; entertainment-social CW and 'practical' love; and 'game-playing' love and both intense-personal and borderline-pathological CW, although these did not retain significance in a multiple regression. McCutcheon et al (2016e) found that participants with higher scores on all three dimensions of CW reported higher levels of dominance, submission, separation, and interactional reactivity during conflict with a romantic partner; higher anxiety in intimate relationships; and were more likely to endorse soulmate beliefs.…”
Section: Romantic Relationship Stylementioning
confidence: 83%
See 1 more Smart Citation
“…In this study, for participants from the USA, 'game-playing' love style was associated with intense-personal CWalthough the two appeared unrelated in participants from India. McCutcheon et al (2016e) noted relationships between intense-personal CW and both 'practical' and 'dependent' love; entertainment-social CW and 'practical' love; and 'game-playing' love and both intense-personal and borderline-pathological CW, although these did not retain significance in a multiple regression. McCutcheon et al (2016e) found that participants with higher scores on all three dimensions of CW reported higher levels of dominance, submission, separation, and interactional reactivity during conflict with a romantic partner; higher anxiety in intimate relationships; and were more likely to endorse soulmate beliefs.…”
Section: Romantic Relationship Stylementioning
confidence: 83%
“…African-American participants tended to choose African-American celebrities as their favoured celebrities, while white participants tended to choose white celebrities. McCutcheon et al (2016e) found that non-white participants scored higher on entertainment-social and intensepersonal CW.…”
Section: Demographicsmentioning
confidence: 91%
“…Second, intense-personal dimension (i.e., moderate level of celebrity worship) represents intense and compulsive feelings toward one’s favorite celebrity (e.g., loss of control over recurring thoughts about a celebrity) ( McCutcheon, Aruguete, Jenkins, McCarley, & Yockey, 2016 ; McCutcheon et al., 2002 ). This dimension has been associated with neuroticism ( Maltby et al., 2003 ), symptoms of depression and anxiety ( Maltby, McCutcheon, Ashe, & Houran, 2001 ), somatic symptoms ( Maltby et al., 2004 ), poor-quality relationships ( McCutcheon, Gillen, Browne, Murtagh, & Collisson, 2016 ), and concerns about body image ( Maltby & Day, 2011 ; Swami, Taylor, & Carvalho, 2009 ). Third, borderline-pathological dimension reflects extreme attitudes and behaviors toward a celebrity that are considered as maladaptive forms of admiration (e.g., if one’s favorite celebrity asked the person to do something illegal as a favor, he/she would do it; McCutcheon, Aruguete, Jenkins, et al., 2016 ; McCutcheon et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…The three participants admitted that the relationship was only limited to idols and fans but the third participant hoped that her future husband would be similar to her idol in terms of both appearance and attitude. Mccutcheon, Gillen, Browne, & Murtagh, (2016) individuals who experience celebrity worship show maladaptive daydreaming, indicating that individuals with an extensive fantasy activity are more likely to be obsessed with celebrities. These psychological constructs have several similarities; for instance, both had a positive association with fantasy proneness.…”
Section: Resultsmentioning
confidence: 99%